Determinants of Government Spending, Its Impact on Public Welfare, and The Role Of Economic Growth: A Literature Review - Nurkodri, Moh Sahroni; Tan, Syamsurijal; Junaidi, Junaidi; Achmad, Erni (PT. Anagata Sembagi Education, 2024)
This study delves into the multifaceted factors that influence government expenditure and its subsequent effects on public welfare, with a particular focus on its impact on economic growth. Government spending plays a pivotal role in shaping economic development, enhancing public welfare, and alleviating poverty. By conducting a systematic literature review, this research methodically evaluates a range of pertinent sources to gain a comprehensive understanding of these dynamics. The findings indicate that strategic government expenditure, particularly in areas such as infrastructure, education, and technology, is instrumental in driving economic growth and improving public welfare outcomes. Investment in infrastructure not only facilitates more efficient business operations but also creates jobs and improves living standards. Similarly, funding education ensures a more skilled workforce, which can foster innovation and productivity. Investments in technology can lead to advancements that spur economic development and enhance quality of life. However, the study also emphasizes that the effectiveness and optimal allocation of government spending are critical factors in realizing these benefits. Effective expenditure strategies, therefore, must be well-planned and targeted. The insights derived from this study provide valuable guidance for policymakers in crafting expenditure strategies that aim to achieve sustainable development and long-term economic stability.